2018
DOI: 10.1186/s40814-018-0334-0
|View full text |Cite
|
Sign up to set email alerts
|

Home-based balance training using Wii Fit™: a pilot randomised controlled trial with mobile older stroke survivors

Abstract: BackgroundSeveral studies have reported that using the Wii™ Balance Board can provide added value regarding balance (re-)training in neurological diseases. However, for the large group of mobile older stroke survivors, there is no evidence regarding the feasibility of an unsupervised Wii™ Balance Board training in the home setting. The aim of this study was to investigate the feasibility of a home-based Wii™ balance training for these patients and to identify methodological challenges for randomised controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 53 publications
(37 reference statements)
0
17
0
1
Order By: Relevance
“…In comparison with other modalities of VR (semi-immersive and non-immersive) such as robotics or Wii games where the patients are trained in a sitting position, our study is based on an immersive VR training protocol which was conducted with the patient in a standing position, increasing the global neuromuscular response. In this sense, previous published studies have used the Wii exergaming to train balance and motor function in stroke patients [21]. Although these studies have shown positive and interesting results, our data suggest that training balance and the global motor function in a standing position is also effective to improve balance after stroke.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In comparison with other modalities of VR (semi-immersive and non-immersive) such as robotics or Wii games where the patients are trained in a sitting position, our study is based on an immersive VR training protocol which was conducted with the patient in a standing position, increasing the global neuromuscular response. In this sense, previous published studies have used the Wii exergaming to train balance and motor function in stroke patients [21]. Although these studies have shown positive and interesting results, our data suggest that training balance and the global motor function in a standing position is also effective to improve balance after stroke.…”
Section: Discussionmentioning
confidence: 50%
“…Nevertheless, the majority of published works have used non-immersive VR therapies, such as Wii exergames for balance training [21,22]. Recently, improved versions of immersive VR have become available for clinical and research purposes in physical rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Telerehabilitation and interactive body motion detection technology using Kinect and Wii Fit have become more popular [ 1 , 2 ]. The COVID-19 is a global pandemic started in the end of 2019 and is still ongoing at the preparation of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of depth camera and body tracking technology and algorithm to identify body joint movements in 3D space (e.g. Realsense, Microsoft Kinect and Microsoft Azure Kinect, Wii Fit), many rehabilitation centers have adapted these affordable 3D motion capture technology to enhance their clinical practice [ 2 , 13 ]. These technologies are being used to make rehabilitation methods more personalized, easy-to-use, and interactive than repetitive and high-intensity training in the traditional setting.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos citam a possibilidade do uso destes sistemas no ambiente domiciliar (onde o treino poderia ser realizado de forma autônoma pelos próprios indivíduos pós-AVE sem a necessidade de um fisioterapeuta direcionando o treinamento), ou ainda citam a possibilidade da aplicação dos exergames em reabilitação sem a supervisão de um fisioterapeuta, reduzindo custos das terapias por não requerer supervisão constante do profissional (Yatar e Yildirim, 2015;Gibbons et al, 2016;Sugarman e Weisel-Eichler, 2009;Deutsch et al, 2009;Viñas-Diz e Sobrido-Prieto, 2016;Laver et al, 2015;Fu et al, 2015). O treino realizado no ambiente domiciliar utilizando este sistema em indivíduos com AVE, no entanto, foi mais estudado com enfoque na função de membro superior (Perrochon et al, 2019) e as evidências ainda não são conclusivas com relação à abordagem voltada ao equilíbrio (Golla et al, 2018;Laufer et al, 2014).…”
Section: Realidade Virtual E Exergamesunclassified